"(S)he's so hearty": Gender cues, stereotypes, and expectations of warmth in peer-to-peer accommodation services. (October 2020) - Pino, Giovanni; Zhang, Carol Xiaoyue; Wang, Ziyou
Highlights: In P2P accommodation platforms, hosts' gender cues affect potential guests' expectations of warmth and booking intentions. Female cues foster higher expectations of warmth than male cues. This effect is seen, in particular, in people with high gender stereotyping tendency. For these people, female cues enhance booking intention via expectations of warmth. Hosts' gender cues do not affect expectations of competence. Abstract: The hospitality industry is witnessing continuous growth in the number of female travellers and female hosts available to accommodate travellers in their properties using peer-to-peer (P2P) service platforms. Cues that convey information about the host's gender are therefore acquiring notable relevance. Tourism research, however, has not yet devoted attention to this phenomenon. To fill this gap, the present paper investigates whether and how gender cues conveyed on P2P accommodation platforms affect users' expectations and booking intentions. Across three experimental studies, the paper demonstrates that such cues affect users' expectations in a P2P accommodation context, but not in a hotel accommodation context. In particular, regardless of the hosts' race, female cues, compared to male cues, appear more able to create expectations of warmth and this effect is evident for users who have a strong gender stereotyping tendency. Importantly, enhanced expectations of warmth exert a positive influence on users' reservation intentions.